2014
DOI: 10.1108/tlo-04-2011-0026
|View full text |Cite
|
Sign up to set email alerts
|

Understanding employee knowledge: the development of an organizational memory scale

Abstract: Purpose – The aim of this study is to develop a psychometrically sound self-report scale of organizational memory. The scale is planned for use in future research to test the relationship between what employees know and their attitudes to passing on their knowledge. Design/methodology/approach – A total of 72 organizational memory scale items representing six hypothesised dimensions of organizational memory were developed and tested with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
0
12
0
5
Order By: Relevance
“…In these searches, the authors found many publications on intellectual capital and human capital, specifically on human capital measurement. The authors found that works like Edvinsson and Malone (1998), Bueno et al (2011), Mention and Bontis (2013), and Dunham and Burt (2014) addressed this issue, but there is still a lack of studies that have validated instruments for human capital dimensioning.…”
Section: Methodological Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In these searches, the authors found many publications on intellectual capital and human capital, specifically on human capital measurement. The authors found that works like Edvinsson and Malone (1998), Bueno et al (2011), Mention and Bontis (2013), and Dunham and Burt (2014) addressed this issue, but there is still a lack of studies that have validated instruments for human capital dimensioning.…”
Section: Methodological Proceduresmentioning
confidence: 99%
“…To fulfil this gap, the authors consider the work of Bueno et al (2011), which shows a way to measure leadership related to human capital. Besides, Dunham and Burt (2014) provide a scale to measure aspects related to organizational memory, applied in New Zealand, that are directly related to human capital. These, if aggregated with the previous one, could assist in measuring a broader perspective of human capital.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire consisted of three sections, The first dealt with demographic information of the research sample, the second section dealt with employee retention strategy, which consists of 40 statements on Positive work environment (5), Employee involvement (5), Compensation & benefits (5), Management support (5), Team working (5), Training & development (5) Employee freedom & flexibility (5) Employee communication ( 5) (Kiruthiga and Magesh, 2014). And the last section dealt with organizational memory which consists of 35 statements on Social knowledge (5), Job knowledge (5) Corporate knowledge (5) Industry knowledge (5) History of the organization (5) Political knowledge (5) Cultural knowledge (5) (Dunham and Burt, 2014). The research uses a five-point rating scale (Likert's Scale).…”
Section: Methodsmentioning
confidence: 99%
“…It was measured through the “human resources indicator approach,” which is a “popular approach” in management and related fields (Mubarik et al, 2018, p. 608). Eight indicator-statements were adapted from the literatures on human capital (Baron, 2011; Dunham & Burt, 2014; Mention & Bontis, 2013; Vidotto et al, 2017). “Human capital” was defined across the statements as newsworkers’ general knowledge, skills and abilities in relation to their jobs.…”
Section: Methodsmentioning
confidence: 99%